The impacts of business process reengineering on organizational control - Neo, Boon Siong (2019)
While the benefits of process integration in business reengineering have been enthusiastically publicized, the impact on organizational control, e.g., the compression of responsibilities and the elimination of checks and control, has received little attention. Inadequate attention to these issues can result in reengineered systems that are exposed to excessive risks or reengineering attempts that are prematurely self-defeating as they contradict the underlying control philosophy. This research seeks to analyze how BPR has changed the controls within an organization. It is primarily motivated by the lack of a theoretical framework within which the disparate control observations from the BPR literature can be examined and reconciled and the lack of focused empirical research on organizational control within a reengineering context.